Broadband and multi angle enhanced antireflection of silicon solar cells by compound random nanostructures. (January 2015) - Yang, Lili; Xuan, Yimin
Abstract: Recent research in nanostructures has shown the potential to effectively enhance light trapping of Si solar cells. In this article, it is demonstrated the decrease of optical reflection in silicon solar cells by a novel random nanostructure, which is combined of the Si random nanostructures (SiRNS) and nanoparticles. The compound random nanostructure is processed by inductively coupled plasma (ICP) and acid solution modification. The reflection of the SiRNS can be substantially reduced due to the graded refractive index. The adding of the nanoparticles to the SiRNS can further suppress the reflection within short wavelength ranges as a result of the excitation of micro-cavity effect and the scattering of light. The averaged reflection of the compound random nanostructured surface is under 6%, when the incident light angle is from 0° to 20°. Therefore, a broadband and multi-angle anti-reflection approach for solar cells is provided. Highlights: A compound random nanostructure is prepared for broadband and multi angle antireflection. The antireflection features of the structured surface are experimentally and theoretically studied. Such a random nanostructure greatly reduces reflection of incident light. The effects of graded refractive index, microcavity, and scattering are coupled.